Studies on the Diversity and impact of Macro Biofouling Organisms in Brackish Water Finfish Cage - Sunithakumari, K.; Joseph, Shoji; Ajithkumar, P. B.; Smina, M. S.; Priya, N. P. (Fishery Technology, 2020)
Biofouling refers to accumulation of organisms on submerged surfaces. In case of open water cage culture, fouling organisms attached to cage nets block water flow and reduces waste removal resulting in increased stress levels on stocked fishes and reduces the rate of intake of feed and growth. It also increases weight of the nets leading to its damage. The quantity and diversity of biofouling organisms and their effects on the growth and survival of stocked fishes were studied. The study was conducted at Moothakunnam, Ernakulam, Kerala. In the present investigation the data is of one culture period (10 months February - November 2017). The water quality parameters observed are: temperature (24.1Â°C to 31.7Â°C), Ph (6.81-7.87), salinity (0-29), light penetration (31.8 cm to 162.475 cm), DO (4.94- 10.528 mg L-1), nitrate (0.016-4.521 mg L-1), nitrite (0 to 0.954 mg L-1), orthophosphate (0.011-0.771 mg L-1) and ammonia (0 to 0.031 mg L-1). Biofouling was found initiated with filamentous algae followed by molluscs dominated by modiolus and other invertebrate organisms. Majority of the fouling organisms observed were molluscs and filamentous algae. Biofouling was highest in areas near the water surface and found reduced with depth. Almost 44.44% of the total net area was affected by biofouling. The total weight of the attachment with net was 3354.88 kg. Macrobiofoulers itself shared a total weight of 658.56 kg and modiolus (90.53%) alone contributed 588.8 kg. Apart from these associated animals like Arthropods, Annelids etc. were also found. Infestation was found increased with salinity and peaked during April-May (29 psu).